Characterization and classification of soils at Jara Gelalicha and Aruma areas, Sidama region, southern Ethiopia - Alemayehu, Habtamu; Haile, Wassie; Kiflu, Alemayehu (Frontiers in Environmental Science, 2025)
IntroductionSoil characterization and classification is a vital tool for classifying soil, identifying soil types, managing nutrient, and transferring research findings. Jara Gelalicha in the Hawassa Zuria district and Aruma in the Wondo Genet district of the Sidama Region require soil characterization and classification. Therefore, this study was carried out in the specified locations to characterize the morphological and physicochemical properties as well as identify the types of soil in the studied areas.MethodsFor this study, extensive preliminary site observations, reconnaissance surveys, and 30 auger observations were conducted before opening the profile pits in each location. One representative pedon was opened at each site to a depth of 2 × 2 × 2 m, and the profiles were described using the Guidelines for Field Soil Descriptions. A total of 12 disturbed and 12 undisturbed soil samples were collected from each diagnostic horizon of both locations.ResultsThe soil analysis result showed that the surface horizon textural class of pedon of Jara Gelalicha was sandy loam; whereas, the textural class of the pedon at Aruma was sandy clay loam. In the Jara Gelalicha and Aruma locations, the OC content in the surface horizons was 2.39% and 3.57%, respectively. In the Jara Gelalicha and Aruma locations, the total nitrogen content of the surface soil horizons was 0.23% and 0.32%, respectively.DiscussionBased on the World Reference Base for Soil Resources, the soils of the study areas classified as Eutric Cambisols (Loamic) in Jara Gelalicha and Eutric Andosols (Loamic) in Aruma area. Therefore, the soil fertility management and land use decision should consider such soil variability. The findings could offer crucial information for designing soil management options to increase soil productivity and to make appropriate land use decision.